Hubungan Pengetahuan dan Sikap Orang Tua Terhadap Status Imunisasi Dasar Lengkap (IDL) di Kota Cirebon - Afrialman, M. Rizal; Adi, Mateus Sakundarno; Martini, Martini (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background : The achievement of Complete Basic Immunization (IDL) status among infants in Cirebon City has not met the strategic plan targets for three consecutive years, from 2020 to 2022. In 2020, the IDL coverage among infants was 83.4%, in 2021 it was 65.5%, and in 2022 it reached 85.3%. This condition is caused by the low level of parental knowledge and attitudes, which leads to neglect in providing Complete Basic Immunization (IDL) for infants. Therefore, the researcher is interested in examining the factors of parental knowledge and attitudes toward the Complete Basic Immunization (IDL) status in Cirebon City.Methods : The research method used is analytical research using a cross-sectional research design. This research was conducted in Cirebon City, West Java. Data collection was carried out in April - May 2024. The data collection technique was purposive sampling. The population in this study is all babies in Cirebon City aged 12-24 months in 2024 with a sample size of 127 respondents.Result : Based on statistical tests, it is known that parental knowledge produces a p value of 0.001 (p<0.05) and parental attitudes produce a p value of 0.001 (p<0.05), meaning that statistically parental knowledge and parental attitudes have a significant relationship. significant impact on Complete Basic Immunization (IDL) status in Cirebon City.Conclusion : The level of parental knowledge and parental attitudes are factors related to achieving Complete Basic Immunization (IDL) status in Cirebon City in 2024.